2018
DOI: 10.1016/j.ejpb.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in carrier mediated nose-to-brain delivery of pharmaceutics

Abstract: Central nervous system (CNS) disorders (e.g., multiple sclerosis, Alzheimer's disease, etc.) represent a growing public health issue, primarily due to the increased life expectancy and the aging population. The treatment of such disorders is notably elaborate and requires the delivery of therapeutics to the brain in appropriate amounts to elicit a pharmacological response. However, despite the major advances both in neuroscience and drug delivery research, the administration of drugs to the CNS still remains e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
215
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(217 citation statements)
references
References 209 publications
1
215
0
1
Order By: Relevance
“…One of the most promising routes of administration appears to be the nose-to-brain targeted drug administration. 5,6 The nasal epithelium is divided into the olfactory and respiratory region. [5][6][7] Drugs that are absorbed through the olfactory region have the potential to avoid systemic elimination (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most promising routes of administration appears to be the nose-to-brain targeted drug administration. 5,6 The nasal epithelium is divided into the olfactory and respiratory region. [5][6][7] Drugs that are absorbed through the olfactory region have the potential to avoid systemic elimination (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…), reach the cerebrospinal fluid (CSF) and accumulate in the brain bypassing the BBB. [5][6][7][8] This route of drug administration is unfortunately limited by low absorption through the olfactory epithelium because of the limited surface area, early enzymatic degradation and rapid ciliary clearance. 9 However, new research has shown that liposomes can optimize nose-to-brain targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug administered by this route can enter the brain principally using olfactory or trigeminal nerve pathways. Moreover, other pathways involving vasculature, cerebrospinal fluid, and the lymphatic system have been individuated [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…[33] Recent developments in the delivery of drugs to the brain, including the use of delivery vehicles such as microand nano-carriers alongside mucoadhesive agents such as chitosan, are promising. [19] In this study, we have investigated the antagonist properties of a synthetic N-terminally truncated and modified human CGRP peptide. We show that ( 34 Pro, 35 Phe) CGRP 27-37 is a potent CGRP receptor antagonist both in vitro and, for the first time, in vivo and demonstrate how it can be formulated for dry powder nasal delivery without loss of potency.…”
Section: Introductionmentioning
confidence: 99%